Vascular management of Hurthle cell carcinoma with internal jugular vein encasement and innominate vein invasion - Samantha Fountain, MMedSci; Sally Tan, MD; Helen Liu, DO; Scott Schubach, MD; John Allendorf, MD; Alec Vaezi, MD; Reese Wain, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
We present a case highlighting innominate vein reconstruction for resection of Hurthle cell carcinoma with complex vascular invasion. A 69-year-old man presented with a rapidly enlarging neck mass, dysphagia and dysphonia. Workup demonstrated a 11.2 × 7.0 × 6.5 cm Hurthle cell carcinoma invading the oropharynx and superior mediastinum. We proceeded with left thyroid lobectomy and modified left radical neck dissection. Median sternotomy, resection of the left clavicular head, and partial resection of the left manubrium were performed to circumferentially expose the innominate vein. Tumor thrombus was extruded from the innominate vein followed by patch angioplasty, which remains patent 14 months postoperatively.